2007
DOI: 10.1139/w06-135
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variability in the FUM1 gene of Fusarium verticillioides strains

Abstract: Fumonisins are mycotoxins, produced mainly by Fusarium verticillioides, that are potentially carcinogenic to humans and toxic to animals. Synthesis of these toxins is directed by a cluster of 15 genes, among which FUM1 is the largest; it encodes a polyketide synthase. This enzyme probably catalyzes the synthesis of a polyketide that forms a large portion of the fumonisin structure. In this study, 27 strains possessing the FUM1 gene, as determined by polymerase chain reaction, were analyzed. A portion of the FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Some F. verticillioides strains have been described as non-fumonisin producers [ 12 , 14 ]. Sánchez-Rangel et al [ 13 ] evaluated 34 F. verticillioides strains isolated from corn in Mexico and found a correlation between the fumonisins production and the presence of the FUM1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some F. verticillioides strains have been described as non-fumonisin producers [ 12 , 14 ]. Sánchez-Rangel et al [ 13 ] evaluated 34 F. verticillioides strains isolated from corn in Mexico and found a correlation between the fumonisins production and the presence of the FUM1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The FUM 1 gene, and other genes of this biosynthetic pathway, has been detected in F. verticillioides isolates through the use of PCR gene amplification techniques [ 11 , 12 , 13 , 14 ]. In order to detect the presence of fungi in plant materials, specific primers in PCR reactions have widely been used.…”
Section: Introductionmentioning
confidence: 99%
“…The observed increased expressions of fum1 , fum15 and fum21 by Ffuji under fumonisin non‐inducing conditions in this study were therefore unexpected and suggests that some fum genes could have other functional roles that are yet to be identified. But, unlike fum1 and fum21 , which have been demonstrated to be essential for the initial steps in the fumonisin biosynthetic pathway (da Silva et al , ), the increased expression of fum15 , which encodes a P450 monooxygenase, both under fumonisin non‐inducing and inducing conditions, suggests that fum15 additionally might play a more important role in fumonisin biosynthesis in F. fujikuroi than previously considered.…”
Section: Discussionmentioning
confidence: 80%
“…The regulation of the biosynthesis of fumonisins has been reported to be modulated by a complexity of genes that include fum1 , fum5 , fum21 , fst1 and Vel1 . The fum1 gene encodes a polyketide synthase and catalyses the initial steps in fumonisin biosynthesis (Bojja et al , ), and the formation of a polyketide that forms a large portion of the fumonisin structure (da Silva et al , ). The fum5 gene is required for fumonisin biosynthesis, the loss of which was reported to result in over 99% reduction in fumonisin production (Proctor et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…While this work was in progress, the use of fum1 as diagnostic target for ‘fumonisin‐producing’ strain detection was also evaluated;36–39 these studies also reported some incomplete correlation of PCR results with in vitro fumonisin production of F. verticillioides . Moreover, da Silva et al 40 found variability among seven F. verticillioides strains sequenced at the fum1 locus and reported failure to obtain the expected amplimer from 11 of the 27 strains tested with their diagnostic primer pair P1/P2. Thus fum1 may not be the best target for the development of diagnostic primers for ‘fumonisin‐producing’ fungi, and the genes coding for the enzymes acting downstream in the fumonisin biosynthetic pathway, responsible for the specificity of the product, may be preferable.…”
Section: Discussionmentioning
confidence: 99%